Test of memory malingering with children: The utility of Trial 1 and TOMMe10 as screeners of test validity. Issue 6 (17th August 2016) - Loughan, Ashlee R.; Perna, Robert; Le, Jessica
Abstract : There is a growing body of research suggesting that the shorter versions of the Test of Memory Malingering (TOMM) may provide an accurate assessment of effort in children. During neuropsychological evaluations, some circumstances result in only one completed trial of the TOMM or partial completion of a trial. Research suggests that a cut-score of 40 or 41 on Trial1 is highly predictive of passing the TOMM overall. In the current study, 194 school-age children with academic and/or behavioral problems were used to compare the accuracy of TOMM1 and TOMMe10 (errors on the first 10 items of TOMM1) in predicting passing/failing of TOMM2. For the children in this sample, a score of < 40 items correct (≥ 10 errors) on TOMM1 was highly accurate in predicting a passing performance on the TOMM2 (sensitivity = .80, specificity = .91) with a Negative Predictive Value = .98 at the malingering base rate of 7% (TOMM2 failure in our sample). A score of 2 errors (8 items correct) on the TOMMe10 was slightly less sensitive than that of the TOMM1 (specificity = .96, sensitivity = .53) but with a similar Negative Predictive Value (.96). Consistent with the research from adult populations, TOMM1 and TOMMe10 appear to be quite accurate in predicting performance on the standard administration of the TOMM and may be useful screeners. However, compared to that found in adult samples, slight differences in suggested cutoffs for TOMM1 and TOMMe10 may be warranted for children.